2019
DOI: 10.1080/15476286.2019.1649585
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced shedding of MICA and HIF1A-mediated immune escape of pancreatic cancer cells from NK cells: role of circ_0000977/miR-153 axis

Abstract: One key to malignant progression of pancreatic cancer (PC) is the acquired ability of tumour cells to escape immune-mediated lysis. Hypoxic microenvironment plays a causal role in PC metastasis. According to previous studies, hypoxia could induce the upregulation of HIF1A, ADAM10 and sMICA, leading to decreased NKG2D in NK cells and tumour cells escape from immune surveillance and NK cellmediated lysis. In the present study, in NK cells derived from high-HIF1A expression patients, the levels of internalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 36 publications
3
106
0
Order By: Relevance
“…In pancreatic cancer cells, hypoxiaassociated pathways conspicuously downregulated membrane MICA while simultaneously increased sMICA expression [84]. This hypoxia-induced sMICA upregulation was attributed to the dysregulated balance between circ_0000977 and miR-153 [84].…”
Section: Mica Mir-20amentioning
confidence: 97%
See 2 more Smart Citations
“…In pancreatic cancer cells, hypoxiaassociated pathways conspicuously downregulated membrane MICA while simultaneously increased sMICA expression [84]. This hypoxia-induced sMICA upregulation was attributed to the dysregulated balance between circ_0000977 and miR-153 [84].…”
Section: Mica Mir-20amentioning
confidence: 97%
“…Ovarian cancer [74] Hepatocellular carcinoma [75,76] Breast cancer [77] Colorectal cancer [78] Gastric cancer [79] miR-93 Hepatocellular carcinoma [76,80] miR-106b Hepatocellular carcinoma [76,80] miR-106a Hepatocellular carcinoma [75] miR-519a-3p Breast cancer [81] miR-125b a Multiple myeloma [82] miR-373 Hepatocellular carcinoma [75] miR-302c Multiple cancers [83] miR-520c Multiple cancers [83] miR-153 b Pancreatic cancer [84] MICB miR-20a Breast cancer [77] Hepatocellular carcinoma [75] miR-373 Hepatocellular carcinoma [75] miR-29a/b/c Hepatocellular carcinoma [75] miR-15b Hepatocellular carcinoma [75] miR-195 Hepatocellular carcinoma [75] miR-16 Hepatocellular carcinoma [75] miR-424 Hepatocellular carcinoma [75] miR-106a Hepatocellular carcinoma [75] miR-107 Hepatocellular carcinoma [75] miR-17 Hepatocellular carcinoma [75] miR-302c Multiple cancers [83] miR-520c Multiple cancers [83] ULBP miR-20a Breast cancer [77] miR-519a-3p Breast cancer [81] miR-302c Multiple cancers [83] miR-520c Multiple cancers [83] MICA (BET) inhibitor could remarkably increase MICA expression on multiple myeloma cells [82]. This BETiinduced MICA elevation was mediated by miR-125b, which targeted the transcription suppressor of MICA (IRF4) [82].…”
Section: Mica Mir-20amentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al further showed that circ-DENND2A was dramatically increased in glioma tissues with high level of HIF1α [55]. Moreover, another study showed that the circ-0000977 level can be induced by hypoxia in pancreatic cancer cells [140]. The axis of circ-0000977/miR-153 can mediate HIF1α-induced immune escape of pancreatic cancer cells through targeting HIF1α/ ADAM10 [140].…”
Section: Circrnas and Hypoxiamentioning
confidence: 99%
“…In addition, we identified transcriptional programs correlated with the non-T cell-inflamed phenotype such as KLF4, HIF1A, KMT2D (alias MLL2), NFE2L2 (alias NRF2), androgen receptor (AR), and estrogen receptor (ER) signaling, which have some literature support for modulating the immune response (Rizvi ;Kovats 2015;Ou et al 2019).…”
Section: Activation Of Transcriptional Programs Correlates With the Nmentioning
confidence: 99%